Seni Kriya : Teknik Dan Kreasi - Suyanto Suyanto (Institut Seni Indonesia Surakarta, 2004)
Craft art is a branch of visual art which is to be functional to meet human needs, both physicaly and spiritualy.Craft art in its development has grown in various regions. As a rule, the product of each region is specific, having different values and characteristics. The material used is also various because Indonesia has many kinds of abundant raw materials.The technique of craft art is a cultural heritage which is well-preserved. Nowadays the technique is not, in fact, firm but flexible to suit the development of the age. The proof is that in order to produce or create good works of art, machines which are technically practical arid effective, are used.A craft work is not created reluctantly but based on an idea or thought. The exi sting concept is used by the artist as a means of facilitating the process of creation. Besides that, the artist requires a high degree of creativity. A highly creative artist is capable to create specific works of art which are unique, disÂtinct, original, innovative, aesthetic and efficient.Keyword:Â Â craft, anggitan